Analisis Buku Matematika SMA Ditinjau dari Pendekatan Saintifik Kurikulum 2013 - Dendy Setyo Anggoro; Sri Sulasteri; A. Sriyanti (Alauddin Journal of Mathematics Education, 2022)
This study aims to determine whether the mathematics textbooks for Class I SMA and MA Curriculum 2013 have been presented in accordance with KI and KD as well as the implementation of a scientific approach. This type of research is a descriptive research that uses a quantitative approach. The research instrument used was a book suitability scoring sheet. The results showed that the Mathematics Textbooks for Class X SMA and MA Curriculum 2013 were presented in accordance with KI and KD and the implementation of a scientific approach, with a percentage of 85.7% or a good category for analysis based on the suitability of the material with KI and KD. The level of conformity with KD from KI-1 is 100% (Very Good), The level of conformity with KD from Kl-2 is 100% (Very Good). The level of conformity with KD from KI-3 is 80% (Good). The level of conformity with KD from 82-4 is 80% (Good). While the percentage of 86.1% or very good category for analysis based on the suitability of the material with the implementation of the scientific approach The implementation of the scientific approach has been reflected in the existence of learning steps through the application of SM (observing, asking questions, digging information, reasoning, and communicating) and discovery learning models learning problem based learning and project hasse learning that have been presented in each chapter.